Analisis Laporan Keuangan Pondok Pesantren Assalafi Al-Fithrah Surabaya berdasarkan ISAK 35 - Laila; Luluk Hanifah (Jurnal Informatika Ekonomi Bisnis, 2024)
The aim of this research is to find out how financial reporting and implementation of financial reports are based on ISAK 35 at the Assalafi Al-Fithrah Islamic boarding school. The method used in this research is a qualitative method using a qualitative descriptive approach. In analyzing financial reports based on ISAK 35, several main foundations underlying ISAK 35 are used, namely, the basic accounting framework, accrual principles, income realization principles, fairness principles, and international accounting standards. The results of this research indicate that the Financial Position report at the Assalafi Al-Fithrah Islamic Boarding School has complied with the ISAK 35 principles in preparing the financial position report; Assalafi Al-Fithrah Islamic Boarding School has not implemented comprehensive income reporting; There are deficiencies in the report on changes in net assets; The cash flow report is in accordance with ISAK 35 principles; The notes to the financial report of the Assalafi Al-Fithrah Islamic Boarding School include a detailed explanation of each account, and this is in accordance with ISAK 35 principles.